Biometric assessment of deep-sea vent megabenthic communities using multi-resolution 3D image reconstructions. (October 2016) - Thornton, Blair; Bodenmann, Adrian; Pizarro, Oscar; Williams, Stefan B.; Friedman, Ariell; Nakajima, Ryota; Takai, Ken; Motoki, Kaori; Watsuji, Tomo-o; Hirayama, Hisako; Matsui, Yohei; Watanabe, Hiromi; et al.
Abstract: This paper describes a method to survey the distribution of megabenthos over multi-hectare regions of the seafloor. Quantitative biomass estimates are made by combining high-resolution 3D image reconstructions, used to model spatial relationships between representative taxa, with lower-resolution reconstructions taken over a wider area in which the distribution of larger predatory animals can be observed. The method is applied to a region of the Iheya North field that was the target of scientific drilling during the IODP Expedition 331 in 2010. An area of 2.5 ha was surveyed 3 years and 4 months after the site was drilled. More than 100, 000 organisms from 6 taxa were identified. The visible effects of drilling on the distribution of megabenthos were confined to a 20 m radius of the artificially created hydrothermal discharges, with the associated densities of biomass lower than observed in nearby naturally discharging areas. Highlights: A method to map megabenthos distribution over multi-hectare regions is described. Habitat maps (>100, 000 ind., 6 species) of the Iheya N. vent field are generated. Cross-species spatial models are used to estimate biomass of a 2.5 ha region. Post-drilling hydrothermal discharges influence the distribution of megabenthos. Megabenthic biomasses in the drilled areas are within naturally occurring levels.